Compatibilization of an immiscible blend of EPDM and POM with an Ionomer. Issue 20 (2nd January 2021) - Bragaglia, Mario; McNally, Tony; Lamastra, Francesca R.; Cherubini, Valeria; Nanni, Francesca
Abstract: Immiscible blends of ethylene‐propylene‐diene‐monomer (EPDM) and polyoxymethylene (POM), when EPDM is the major phase were compatibilized on the addition of an ionomer, poly(ethylene‐co‐methacrylic acid). The inclusion of the ionomer reduced the interfacial tension between the two phases, such that the diameter of the POM domains were significantly reduced to between 0.5 and 2 μm, typical of that required to toughen ductile polymers. The mechanical properties of the resultant compatibilized blends were significantly enhanced with increases in Young's modulus (↑54%), tensile strength ( σ, ↑139%), elongation at break ( ε, ↑97%), and tensile toughness (↑500%) with increasing ionomer content, relative to EPDM rubber alone. The ShoreA hardness of the compatibilized blend was 70.1 compared with 56.8 for the immiscible binary blend and, 50.2 for neat EPDM rubber. Abstract : Compatibilization of polyoxymethylene (POM, yellow spheres) in ethylene‐propylene‐diene‐monomer (EPDM, light blue major phase) via the addition of poly(ethylene‐co‐methacrylic acid) ionomer. The inclusion of the ionomer reduced the interfacial tension between EPDM and POM phases.